Associated Factors Related to Self-Management Behaviors among People with Type 2 Diabetes in Myanmar - Oo, Aye Nyein; Lininger, Jiraporn; Leelacharas, Sirirat (Makara Journal of Health Research, 2023)
Background: Diabetes is a global health concern that affects individuals and the healthcare system. This study aimed to describe the relationships between personal and environmental factors and self-management behaviors in individuals with type 2 diabetes mellitus (T2DM). Methods: This research included 100 individuals with T2DM who were recruited through convenient sampling from three government hospitals in Myanmar. Data collection was fulfilled using a standardized interviewer-administered questionnaire consisting of demographic information, the Diabetes Management Self-Efficacy Scale, the New Short-Form Health Literacy Instrument, the 24-item version of the Diabetes Knowledge Questionnaire, the Social Support Questionnaire, and the Summary of Diabetes Self-care Activity. Data analysis was conducted using descriptive statistics, Chi-square, Pearson’s correlation, and Spearman’s rho correlation coefficient. Results: Self-efficacy (r = 0.375, p < 0.01), health literacy (r = 0.43, p < 0.01), diabetes knowledge (r = 0.461, p < 0.01), and social support (r = 0.337, p < 0.01) were significantly related to self-management behavior. Conclusions: This study indicates the importance of enhancing self-management behaviors, self-efficacy, health literacy, diabetes knowledge, and social support for individuals diagnosed with type 2 diabetes. Future studies should focus on the prediction or interventions to explore the relationship between personal and environmental factors and self-management behaviors among T2DM individuals in Myanmar.